The correlation of urinary strontium with the risk of chronic kidney disease among the general United States population - Zhang, Fenglian; Hu, Na; Li, Jiayue; Pu, Ming; Li, Xinchun; Li, Yuanmei; Liao, Dan (Frontiers in Public Health, 2023)
Background: This study sought to illustrate whether urinary strontium levels were related to developing chronic kidney disease (CKD) in the United States population.Methods: A total of 5,005 subjects were identified from the National Health and Nutrition Examination Survey 2011-2016. Survey-weighted logistic regression analysis, multivariate linear regression analysis, restricted cubic spline (RCS) plots curve and stratified analyses were undertaken to explicate the correlation between urinary strontium and CKD.Results: With the increase of urinary strontium, the incidence rate of CKD and urinary albumin to creatinine ratio (UACR) levels gradually decreased, and estimated glomerular filtration rate (eGFR) levels gradually increased. After controlling all confounders, only urinary strontium in the fourth quartile was correlated to a lower CKD prevalence (OR: 0.59; 95% CI, 0.44-0.79) compared to the lowest quartile. Multivariate linear regression analysis showed that urinary strontium was positively correlated with eGFR but negatively with UACR. RCS curve suggested a nonlinear relationship between urinary strontium and CKD (P for non-linearity < 0.001).Stratified analyses indicated no significant difference in the correlation between urinary strontium and CKD among different subgroups.Urinary strontium was strongly correlated with a low risk of CKD, and this association was non-linear among the US population.